Varicella zoster virus triggering Henoch–Schonlein Purpura in an adult: A case report - Kevin Chung; Natasha Priya Dyal; Sandhya Nagarakanti (IDCases)
This case reports highlights a 37-year-old woman who was transferred to Mayo Clinic Arizona for care after development of seizures, altered mental status, and a diffuse petechial rash, along with vesicular lesions near the groin. She received broad-spectrum antimicrobial therapy. CSF testing showed lymphocytic pleocytosis and elevated protein levels, and PCR testing confirmed varicella zoster virus (VZV) infection. MRI of the brain demonstrated chronic microhemorrhages, indicative of vasculitis secondary to disseminated VZV. Dermatology consultation and subsequent biopsy of the skin lesions revealed leukocytoclastic vasculitis with IgA deposition, consistent with Henoch-Schonlein Purpura (HSP). A VZV-positive PCR from the rash further corroborated the diagnosis. This case highlights the first reported instance of VZV induced HSP in an adult. Although this patient had no complications from HSP, early recognition and targeted treatment are necessary in some cases to prevent severe conditions. This case underscores the importance of maintaining a broad differential diagnosis and the importance of biopsy lesions for prompt recognition of uncommon conditions in high-risk patients.